Screening Drought Tolerance Criteria in Maize - Kiani, Masoud (Asian Journal of Agriculture and Rural Development, 2013)
Six pure lines of maize were tested in a randomized complete block design with three replication under irrigated and rainfed conditions. Genetic variation was found between the genotypes for yield potential (Yp) stress yield (Ys), tolerance index (TOL), geometric mean productivity (GMP), harmonic mean (HM) and stress tolerance index (STI). Stress tolerance index was corrected using a correction coefficient (Ki) and thus a modified stress tolerance index (MSTI) was introduced as the optimal selection criterion for drought-tolerant genotypes. The results of three-D plotting indicated that the most desirable genotype for irrigated and rainfed conditions was the genotype K1515, for non-stressed conditions K18 and for stress conditions K104/3, K760/7 and K126/10.